Advances in food science and technology - P. M., Visakh; Thomas, Sabu; Iturriaga, Laura B.; Ribotta, Pablo Daniel (Wiley ; Scrivener Publishing, 2013)
"This book comprehensively reviews research on new developments in all areas of food chemistry/science and technology. It covers topics such as food safety objectives, risk assessment, quality assurance and control, good manufacturing practices, food process systems design and control and rapid methods of analysis and detection, as well as sensor technology, environmental control and safety. The book focuses on food chemistry and examines chemical and mechanical modifications to generate novel properties, functions, and applications."--Resumé vydavatele